The future of the artificial kidney: moving towards wearable and miniaturized devices - Ronco, C; Davenport, A; Gura, V (Nefrologia : publicacion oficial de la Sociedad Espanola Nefrologia, 2011)
New directions in dialysis research include cheaper treatments, home based therapies and simpler methods of blood purification. These objectives may be probably obtained with innovations in the field of artificial kidney through the utilization of new disciplines such as miniaturization, microfluidics, nanotechnology. This research may lead to a new era of dialysis in which the new challenges are transportability, wearability and why not the possibility to develop implantable devices. Although we are not there yet, a new series of papers have recently been published disclosing interesting and promising results on the application of wearable ultrafiltration systems (WUF) and wearable artificial kidneys (WAK). Some of them use extracorporeal blood cleansing as a method of blood purification while others use peritoneal dialysis as a treatment modality (ViWAK and AWAK.) A special mention deserves the wearable/portable ultrafiltration system for the therapy of overhydration and congestive heart failure (WAKMAN). This system will allow dehospitalization and treatment of patients with less comorbidity and improved tolerance. On the way to the wearable artificial kidney, new discoveries have been made such as a complete system for hemofiltration in newborns (CARPEDIEM). The neonate in fact is the typical patient who may benefit from miniaturization of the dialysis circuit. This review analyzes the rationale for such endeavour and the challenges to overcome in order to make possible a true ambulatory dialysis treatment. Some initial results with these new devices are presented. We would like to stimulate a collaborative effort to make a quantum leap in technology making the wearable artificial kidney a reality rather than a dream.